1980
DOI: 10.1113/jphysiol.1980.sp013511
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lithium on electrolyte transport by the in situ choroid plexus of the cat.

Abstract: SUMMARY1. The effects of lithium on electrolyte transport were studied by using the cat choroid plexus isolated in a chamber in situ.2. Lithium infused intravenously to produce plasma lithium concentrations up to 5 m-equiv/l. caused an increase in plasma magnesium with no effect on the concentration of magnesium in the chamber fluid.3. When 22NaCl was infused intravenously the chamber fluid/plasma ratio of 22Na was nearly 1 in the first 30 min sample and at the steady state it was significantly greater than 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
1
Order By: Relevance
“…The lack of effect of Li+ on sodium efflux (Fig. 3) is inconsistent with observations of Reed & Yen (1980) on the effect of 22Na transport across a cat choroid plexus preparation. They found that Li+ increased the 22Na content of fluid bathing the choroid plexus.…”
Section: Ipcontrasting
confidence: 86%
“…The lack of effect of Li+ on sodium efflux (Fig. 3) is inconsistent with observations of Reed & Yen (1980) on the effect of 22Na transport across a cat choroid plexus preparation. They found that Li+ increased the 22Na content of fluid bathing the choroid plexus.…”
Section: Ipcontrasting
confidence: 86%
“…Therefore, the results from investigations of different species consistently found that Li in CSF stimulated plasma Na (and presumably water) turnover into the ventricles. 43 Overall, these findings of increased Na transport by choroid plexus, and the putatively excessive CSF formation in a state of Li loading, suggest that the Na-transport inhibitors (e.g., amiloride, acetazolamide-congeners, and spironolactone) deserve further consideration as therapeutic agents to reduce the elevated ICP of PTCS in children and adults. [1][2][3][4][5][6] Fluid-Transport Modeling of Pseudotumor Cerebri Syndrome: Proposed Future Opportunities Assessing plasma Na flux into central nervous system is key to understanding PTCS pathophysiology and pharmacologic remediation.…”
Section: Interaction Of LI With Na Transport In Choroid Plexusmentioning
confidence: 86%
“…Similarly to BBB, Na related transporters/channels might be also involved in the Li transport across the BCSFB [94,95] (Figure 2). NHE1 is not expressed in the human choroid plexuses, while it is still unknown whether the other NHE isoforms (such as NHE5) are expressed or not [96][97][98][99].…”
Section: Transport Mechanisms Of Lithium Across the Bbb And Bcsfbmentioning
confidence: 99%